Pulp regeneration as endodontic treatment in necrotic teeth with incomplete rhizogenesis - Bontempo, Hizabelle Prudente (2023)
The treatment of teeth with incomplete root formation and pulp necrosis is challenging for the dentist, because these teeth have thin walls that make the chemical-mechanical preparation difficult, and the risk of fracture of these immature teeth is high, not presenting a favorable prognosis. Thus, the search for new treatment alternatives is constant, in order to close the apical foramen without weakening these teeth. The aim of this work, through a literature review, was to conduct an analysis of studies that address pulp regeneration as an endodontic treatment in necrotic teeth with incomplete root formation, in order to conceptualize and present the main characteristics, understanding how pulp regeneration can become an alternative endodontic treatment. For this, the search for studies was conducted in databases such as Google Scholar, Scielo and Pubmed, in which 25 articles in English, Portuguese or Spanish were selected. As a result it was possible to understand that pulp regeneration is a simple technique, and that a good rate of acceptance is expected, becoming a first approach technique for the endodontic treatment of teeth with necrotic incomplete rhizogenesis.